Ultrasonic Technology for Management of Primary Spontaneous Pneumothorax - Fiorelli, Alfonso; Mazzella, Antonio; Accardo, Marina; Santini, Mario (The Thoracic and Cardiovascular Surgeon, 2017)
To manage primary spontaneous pneumothorax, we use an alternative technique for bleb resection and we induce pleurodesis with an ultrasonic-driven scalpel. This technique was successfully performed in nine consecutive patients with primary spontaneous pneumothorax with small (<20 mm) and limited number of blebs (<2) and without significant underlying lung disease. After identification of air leakage, the jaws of the instrument were clamped onto the bleb and included a margin of normal lung. Power level 3 energy was applied to resect the bleb and to seal the parenchyma. Finally, the parietal pleura was partially scarified using the same instrument to achieve pleurodesis. Histologic findings showed complete sealing of the resection line by coagulative tissue.
Keywords: pneumothorax; thoracoscopy/VATS; ultrasonic; all applications